Tanggung Jawab Pendidik Dalam Perspektif Hadits - Malik Adharsyah Syarifuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Education is one of the most crucial factors for a child’s development. An educated child reflects an educated mindset and behavior pattern. Conversely, an uneducated child will demonstrate an uneducated way of thinking and behaving. Good education acts as a foundation that shapes a child’s bright future. Education is not merely limited to subjects within the curriculum, such as mathematics or history, but also encompasses the development of a child’s character. Educators hold the responsibility of carrying out the educational process. This article examines in depth the responsibility of educators from the perspective of the hadiths of the Prophet Muhammad (peace be upon him), as an ethical, spiritual, and moral foundation in building an integral Islamic education system. The focus of this study lies in exploring the concept of mas'uliyyah (accountability) in the hadiths and how these principles construct a framework for educators in nurturing a generation of faith and virtue. The methodology employed is a qualitative descriptive approach through the examination of classical and contemporary literature. The findings indicate that the hadiths emphasize the educator’s role not merely as a teacher, but more profoundly as a moral leader and guardian of the students’ innate nature (fitrah), bearing responsibility both vertically to Allah and horizontally to society. This study recommends the integration of prophetic values into the curriculum and practice of Islamic education, particularly within the contexts of family, school, and social environment as spaces for holistic character formation.